A Versatile Approach for the Site‐Specific Modification of Recombinant Antibodies Using a Combination of Enzyme‐Mediated Bioconjugation and Click Chemistry1. Issue 26 (11th May 2015) - Alt, Karen; Paterson, Brett M.; Westein, Erik; Rudd, Stacey E.; Poniger, Stan S.; Jagdale, Shweta; Ardipradja, Katie; Connell, Timothy U.; Krippner, Guy Y.; Nair, Ashish K. N.; Wang, Xiaowei; Tochon‐Danguy, Henri J.; et al.
Abstract A unique two‐step modular system for site‐specific antibody modification and conjugation is reported. The first step of this approach uses enzymatic bioconjugation with the transpeptidase Sortase A for incorporation of strained cyclooctyne functional groups. The second step of this modular approach involves the azide–alkyne cycloaddition click reaction. The versatility of the two‐step approach has been exemplified by the selective incorporation of fluorescent dyes and a positron‐emitting copper‐64 radiotracer for fluorescence and positron‐emission tomography imaging of activated platelets, platelet aggregates, and thrombi, respectively. This flexible and versatile approach could be readily adapted to incorporate a large array of tailor‐made functional groups using reliable click chemistry whilst preserving the activity of the antibody or other sensitive biological macromolecules.